Morbi-Mortalidade Juvenil por Acidentes de Transporte em Goiânia Goiás - CAIXETA, Carlos Roberto (2006)
Transport accidents are currently one of the world s main public health problems. The aim of this investigation is to describe the profile of transport injury victims attended at Hospital de Urgências de Goiânia (HUGO) and of victims who deceased in these accidents, with age 15 to 24 years, residents in Goiânia, Goiás - Brazil. It also describes the circumstances involved in these accidents. This descriptive transversal study was carried out in the city of Goiânia from August 2005 to August 2006 with systematic sampling, considering the day of the week and the time of the day. At that period were interviewed 301 victims attended at HUGO, the main Emergency Service Center of the city, and the family of 62 cases of death occurred in the municipality. The data were treated by descriptive statistics. Most victims attended at HUGO and most of those who died were male, mean age 19.94 ± 2.73 years. The main transport used by the victims attended at HUGO was the motorcycle (67.33%), followed by the bicycle (16.67%). The motorcycle was the most used by fatal victims (66.67%) as well. The accidents usually occurred at night, especially around 6 pm to 9 pm and at weekends (fridays and sundays). The victims were generally on the way to do physical, sportive, school, leisure or entertaining activities at that time. Those who were doing paid work had the accident between 6 am and 9 am. Suspicion of alcohol use was confirmed in 15.16% of the cases attended at HUGO and by 26.31% of the family of fatal victims. The victims attended at HUGO were the drivers in 77.11% of the motorcycle accidents and 92.00% of bicycle accidents, as well as in 76.92% of the fatal victims. There were victims under 18 years of age identified as drivers of automobiles and motorcycles. In proportion (p<0.05), more motorcyclists (66.48%) believed that there was imprudence/ negligence than the cyclists (47.72%) attended at HUGO. Security equipment was not used by 8.58% of motorcyclists, by 95.45% of cyclists attended at HUGO and by 12.5% of the motorcyclists who died. The safety belt was not used by 50.00% of the attended at HUGO and by 60.00% of who died. The results indicate a need for a differentiated look at motorcyclists, which justifies a specific approach to this group, as well as measures of inspection, giving priority to the periods of night and weekends. The service of attending victims must be planned, adjusting the amount of human, material and equipment resources, and the seasonality of accidents. The epidemiologic profile of the victims provides important information for administrators to implement politics of promoting health and preventing injury transport, which takes intersectional and multiprofessional actions to confront the problem. Keywords: Transport accidents are currently one of the world s main public health problems. The aim of this investigation is to describe the profile of transport injury victims attended at Hospital de Urgências de Goiânia (HUGO) and of victims who deceased in these accidents, with age 15 to 24 years, residents in Goiânia, Goiás - Brazil. It also describes the circumstances involved in these accidents. This descriptive transversal study was carried out in the city of Goiânia from August 2005 to August 2006 with systematic sampling, considering the day of the week and the time of the day. At that period were interviewed 301 victims attended at HUGO, the main Emergency Service Center of the city, and the family of 62 cases of death occurred in the municipality. The data were treated by descriptive statistics. Most victims attended at HUGO and most of those who died were male, mean age 19.94 ± 2.73 years. The main transport used by the victims attended at HUGO was the motorcycle (67.33%), followed by the bicycle (16.67%). The motorcycle was the most used by fatal victims (66.67%) as well. The accidents usually occurred at night, especially around 6 pm to 9 pm and at weekends (fridays and sundays). The victims were generally on the way to do physical, sportive, school, leisure or entertaining activities at that time. Those who were doing paid work had the accident between 6 am and 9 am. Suspicion of alcohol use was confirmed in 15.16% of the cases attended at HUGO and by 26.31% of the family of fatal victims. The victims attended at HUGO were the drivers in 77.11% of the motorcycle accidents and 92.00% of bicycle accidents, as well as in 76.92% of the fatal victims. There were victims under 18 years of age identified as drivers of automobiles and motorcycles. In proportion (p<0.05), more motorcyclists (66.48%) believed that there was imprudence/ negligence than the cyclists (47.72%) attended at HUGO. Security equipment was not used by 8.58% of motorcyclists, by 95.45% of cyclists attended at HUGO and by 12.5% of the motorcyclists who died. The safety belt was not used by 50.00% of the attended at HUGO and by 60.00% of who died. The results indicate a need for a differentiated look at motorcyclists, which justifies a specific approach to this group, as well as measures of inspection, giving priority to the periods of night and weekends. The service of attending victims must be planned, adjusting the amount of human, material and equipment resources, and the seasonality of accidents. The epidemiologic profile of the victims provides important information for administrators to implement politics of promoting health and preventing injury transport, which takes intersectional and multiprofessional actions to confront the problem.